Knowledge-Enhanced Scene Graph Generation with Multimodal Relation Alignment (Student Abstract) - Fu, Ze; Feng, Junhao; Zheng, Changmeng; Cai, Yi (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
Existing scene graph generation methods suffer the limitations when the image lacks of sufficient visual contexts. To address this limitation, we propose a knowledge-enhanced scene graph generation model with multimodal relation alignment, which supplements the missing visual contexts by well-aligned textual knowledge. First, we represent the textual information into contextualized knowledge which is guided by the visual objects to enhance the contexts. Furthermore, we align the multimodal relation triplets by co-attention module for better semantics fusion. The experimental results show the effectiveness of our method.